Homocoupling of Phenylboronic Acid using Atomically Dispersed Gold on Carbon Catalysts: Catalyst Evolution Before Reaction. Issue 8 (2nd March 2018) - Parmentier, Tanja E.; Dawson, Simon R.; Malta, Grazia; Lu, Li; Davies, Thomas E.; Kondrat, Simon A.; Freakley, Simon J.; Kiely, Christopher J.; Hutchings, Graham J.
Abstract: Coupling reactions to form new C−C bonds are extensively used in industrial synthetic processes. Gold has been shown to be an active catalyst for such reactions; however, conflicting reports exist as to whether cationic Au or metallic Au acts as the active species. We prepared a heterogeneous catalyst consisting of atomically dispersed Au–Cl x supported on carbon and showed this to be active in the homocoupling of phenylboronic acid to biphenyl. However; characterisation of the catalyst materials, even after just a short exposure time to the reactants, revealed rapid reduction and sintering of the Au species into larger metallic nanoparticles, which we propose to be the true active species in this instance. This study suggests that if cationic Au is an active catalyst, it must be stabilised against reduction and agglomeration by either forming complexes which are more stable than common chlorides or by strongly anchoring them firmly onto alternative support materials; as in this case the carbon supported Au–Cl species were easily reduced. Abstract : Growing big(ger) : Atomically dispersed Au–Cl x supported on carbon is active in the homocoupling of phenylboronic acid. However, even after just a short exposure time to the reactants, rapid reduction and sintering of the Au species into larger metallic nanoparticles occurs, which are proposed to be the true active species.